Apocrypha Hiberniae - Breatnach, Caoimhín; Breatnach, Caoimhín; McNamara, Martin 1930-; Breatnach, Pádraig A.; Carey, John; Carey, John; Flahive, Joseph; Flahive, Joseph; Mac Gearailt, Uáitéar; Ó Dochartaigh, Caitríona; Poppe, Erich 1951-; Wright, Charles Darwin 1954-; et al. (Brepols, 2023)
"The present volume, the continuation of volume CCSA 21, comprises further editions, by several of the major scholars now working in the field of medieval Irish apocrypha, of a selection of important eschatological texts. The first of these, Bráth, níba bec a breisim, edited by Erich Poppe, concerns the events which will occur on the Day of Judgement. Caitríona Ó Dochartaigh provides edition, translation and a commentary of Poems 153-162 of Saltair na Rann, an independent eschatological composition. Prof. Uáitéar Mac Gearailt publishes a study and a commented edition of Scéla Laí Brátha, Tidings of the Day of Judgement. Prof. Caoimhín Breatnach publishes Garbh éirghid iodhain bhrátha, Harshly do the pangs of Doomsday, as well as two short Irish texts on the Fifteen Signs Before Doomsday and on Doomsday. Prof. Pádraig A. Breatnach provides the edition of A Tract on the Fifteen Signs of Doomsday. Fr Martin McNamara MSC publishes two short studies in Appendices: the first one on the duration of the Day of Doom (The Day of Doom a Thousand Years, in Appendix 1); the second one concerns a quotation in the Fifteen Signs text edited by Caoimhín Breatnach from the 15th-century Latin theologian Pelbartus (Passage from Pelbartus, Advent Sermon IV: Appendix 2). Fr McNamara also introduces the collection with a discussion of "The Signs before Doomsday". "
Keywords: Quelle